Aluminum and manganese tolerance of wheat (Triticum aestivum L.) cultivars: I. screening for aluminum tolerance - Brauner, J.L.; Sarruge, J.R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
Thirty wheat cultivars were evaluated by means of cultures in nutritive solutions containing 0.0. (check), 2.5, 5.0, 7.5 and 10.0 ppm of Al, under greenhouse conditions. After 12 days in the nutritive solutions, the length and dry matter weight of roots, as well as dry matter weight, of aerial parts were measured. Considering as 100% the data estimated from the check treatments, the Al concentrations needed to produce 80% of dry matter (roots and aerial parts) and root length were calculated through regression equations. According to the results, 4 groups of tolerance were established.